Potential Analysis And Optimalize Strategy Of Boarding Home Tax In Banyuwangi District: Potential Analysis And Optimalize Strategy Of Boarding Home Tax In Banyuwangi District - Yeni Puspita; Galih Wicaksono (Jurnal Mantik, 2020)
The purpose of this research is to determine the potential of a boarding house tax and tax revenue optimization strategies boarding house at Banyuwangi Regency. The analytical method uses a quantitative approach to give a questionnaire to the boarding house owner as a taxpayer. Based on information from four sub-districts can be concluded that the total potential of boarding house tax in the Banyuwangi Regency is IDR 717,755,450.00. The strategy needs to be done by the local government to increase boarding house tax revenue are through optimizing the intensification of local tax collection, strengthening the collection process, increasing supervision, increasing administrative efficiency and reducing collection costs. This can be done by increasing coordination with related institutions in the region. The analytical method is used as a quantitative approach to give a questionnaire to the boarding house owner as a taxpayer